Day of infamy - Lord, Walter, 1917-2002. (Ware, Hertfordshire : Wordsworth Editions, 1998)
Walter Lord interviewed nearly 600 particpants in the tragic and treacherous attack on the USA's prime Pacific Ocean naval base in the Hawaiian Islands. This text presents the authentic picture.
"Isn't That a Beautiful Sight?" -- "A Dream Come True!" -- "Gate Open -- White Lights" -- "You'd Be Surprised What Goes on Around Here" -- "Well, Don't Worry About It" -- "Joe, This is One for the Tourist!" -- " I Didin't Even Know They Were Sore at Us" -- "I Can't Keep Throwing Things at Them" -- "You Don't Wear a Tie to War" -- "I Want Three Volunteers: You, You, and You " -- "Chief, My Mother and Dad Gave Me This Sword" -- "We're Leaving Now- Explode Gloriously!"
Originally published: London : Longmans, Green, 1957.
Includes bibliographical references (pages 221-224) and index.
Keywords: 1941; Pearl Harbor (Hawaii), Attack on, 1941.; Pearl Harbor, Attaque sur, 1941.; Hawaii